Cross-border exchange and sharing of generation reserve capacity - Fridrik Már Baldursson; Ewa Lazarczyk; Marten Ovaere; Stef Proost (Research Institute of Industrial Economics (IFN), 2017)
This paper develops a stylized model of cross-border balancing. We distinguish three degrees of cooperation: autarky, reserves exchange and reserves sharing. The model shows that TSO cooperation reduces costs. The gains of cooperation increase with cost asymmetry and decrease with correlation of real-time imbalances. Based on actual market data of reserves procurement of positive and negative automatic frequency restoration reserves in Belgium, France, Germany, the Netherlands, Portugal and Spain, we estimate the procurement cost decrease of exchange to be 160 million euro per year and of sharing to be 500 million euro per year. The model also shows that voluntary cross-border cooperation could be hard to achieve, as TSOs do not necessarily have correct incentives.
Keywords: L94; D61; C78; 330; Cross-border balancing; Generation reserves; Multi-TSO interactions; Electricity transmission reliability